Education System of Different Types of Schools in India: A Focus on Learning and Student-centered Approaches in India's Education System (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The school system in India should focus on learning rather than on exams. In accordance with its interests, children must be permitted to select matters. Children should engage in groups and voice their opinions on different subjects, rather than acquiring information through extensive books and lectures. Children must instead be taught to seek for knowledge from library books and the Internet on their own and share it in the classroom instead of taking notes from teachers or textbooks. This helps students to establish excellent reading habits, confidence and critical receptivity. It helps students also to build critical reading and analytical abilities. When they apply it realistically, children are able to recall what they learn. They must go on field excursions to museums, laboratories, planetariums, sites for excavation, botanical gardens, etc., where they may learn via contacts with experts in other areas. Their communication abilities will also improve. The author of this essay would want to concentrate on our country's basic education system.